Death as a symbolic way to achieve freedom in ‘The story of an hour’ by Kate Chopin and ‘Sweat’ by Zora Neale Hurston - Rojas Muñoz, Madeleine (Universidad de Santiago de Chile, 2015)
Integrantes: Madeleine Rojas Muñoz, Scarlette Soto Bravo, Camila Suazo Monrós, Karen Valenzuela González
Keywords: Chopin, Kate, 1851-1909 - Crítica e Interpretación; Hurston, Zora Neale, 1891-1960 - Crítica e interpretación; Muerte en literatura